2001
DOI: 10.5038/1827-806x.30.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of calcium carbonate in karst caves: role of bacteria in Stiffe's Cave

Abstract: Bacteria make a significant contribution to the accumulation of carbonate in several natural habitats where large amounts of carbonates are deposited. However, the role played by microbial communities in speleothem formation (stalactites, stalagmites etc.) in caves is still unclear. In bacteria carbonate is formed by autotrophic pathways, which deplete CO 2 from the environment, and by heterotrophic pathways, leading to active or passive precipitation. We isolated cultivable heterotrophic microbial strains, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Some evidence exists that Acidobacteria are capable of methylotrophic growth (42), which may be an ecological advantage in an oligotrophic habitat with low inputs of organic matter. A number of cultivation-based investigations reported that diverse groups of Gram-positive bacteria inhabit cave environments (13,26,35,45). However, the two Gram-positive phyla (Firmicutes and Actinobacteria) in our libraries were detected at a relatively low abundance.…”
Section: Discussionmentioning
confidence: 65%
“…Some evidence exists that Acidobacteria are capable of methylotrophic growth (42), which may be an ecological advantage in an oligotrophic habitat with low inputs of organic matter. A number of cultivation-based investigations reported that diverse groups of Gram-positive bacteria inhabit cave environments (13,26,35,45). However, the two Gram-positive phyla (Firmicutes and Actinobacteria) in our libraries were detected at a relatively low abundance.…”
Section: Discussionmentioning
confidence: 65%
“…Indirect effects arise when the microbes induce calcite precipitation by modifying the local environment through their metabolic processes (e.g., Newman 2003, 2005;Barton and Northup 2007). That microbes can indirectly induce CaCO 3 precipitation and influence the mineralogy and morphology of the precipitated crystals has been well documented in numerous experiments (Ercole et al 2001;Groth et al 2001;Cacchio et al 2003;Rautaray et al 2003;Sanchez-Moral et al 2003;Ahmad et al 2004;Cacchio et al 2004;Rautaray et al 2004;Baskar et al 2006). Crystals precipitated in this manner do not exhibit any evidence of microbial influence, although Rautaray et al (2003Rautaray et al ( , 2004 noted that they may contain proteins indicative of the causative microbes.…”
Section: Discussionmentioning
confidence: 93%
“…Possible influences on the CaCO 3 precipitation could include the colder temperatures which increases the CO 2 solubility (Garrels & Christ, 1965;Langmuir, 1997;Ford & Williams, 2007). The presence of heterotrophs and other microbial metabolism activities may alter the alkalinity (Ercole et al, 2001;Dupraz et al, 2008). No evidence of dissolution or fungal boring at the microscopic scale was seen.…”
Section: +mentioning
confidence: 99%
“…In general, mineralogy and crystal shape is a function of the environment in which precipitation occurs (Ercole et al, 2001;Dove et al, 2003). This may include extrinsic factors such as physiochemical processes, and intrinsic microbial processes, such as respiration or production of organic molecules (Dupraz et al, 2008).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation